Celiac Disease and Gluten-Free Oats: A Canadian Position Based on a Literature Review. (24th February 2016) - La Vieille, Sébastien; Pulido, Olga M.; Abbott, Michael; Koerner, Terence B.; Godefroy, Samuel
Abstract : This paper provides an overview of the latest scientific data related to the safety of uncontaminated oats (<20 ppm of gluten) in the diet of individuals with celiac disease (CD). It updates the previous Health Canada position posted on the Health Canada website in 2007 and a related paper published in 2009. It considers a number of recent studies published between January 2008 and January 2015. While recognizing that a few people with celiac disease seem to be clinically intolerant to oats, this review concludes that oats uncontaminated by gluten-containing cereals (wheat, rye, and barley) can be safely ingested by most patients with celiac disease and that there is no conclusive evidence that the consumption of uncontaminated or specially produced oats containing no greater than 20 ppm gluten by patients with celiac disease should be limited to a specific daily amount. However, individuals with CD should observe a stabilization phase before introducing uncontaminated oats to the gluten-free diet (GFD). Oats uncontaminated with gluten should only be introduced after all symptoms of celiac disease have resolved and the individual has been on a GFD for a minimum of 6 months. Long-term regular medical follow-up of these patients is recommended but this is no different recommendation to celiac individuals on a GFD without oats.